2021
DOI: 10.1186/s40462-021-00297-z
|View full text |Cite
|
Sign up to set email alerts
|

Movement and dispersal of a habitat specialist in human-dominated landscapes: a case study of the red panda

Abstract: Background Habitat specialists living in human-dominated landscapes are likely to be affected by habitat fragmentation and human disturbances more than generalists. But there is a paucity of information on their response to such factors. We examined the effect of these factors on movement patterns of red pandas Ailurus fulgens, a habitat and diet specialist that inhabits the eastern Himalaya. Methods We equipped 10 red pandas (six females, four ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 91 publications
0
5
0
Order By: Relevance
“…The major objective of this study was to evaluate the roles of geo-physical, vegetation, and disturbance covariates on seasonal resource selection patterns of red pandas in a human-dominated landscape. Given their low ecological plasticity, and seasonal variation in movement ( Yonzon 1989 ; Reid et al 1991 ; Zhang et al 2009 ; Bista et al 2021b ) and space use patterns ( Yonzon 1989 ; Reid et al 1991 ; Bista et al 2022a ), we hypothesized a different degree of response to geo-physical, vegetation, and disturbance variables across seasons. We predicted that vegetation-related variables would be more important determinants of habitat utilization than geo-physical variables (such as elevation, aspect, slope, topographic position index [TPI], solar radiation, and water).…”
mentioning
confidence: 99%
“…The major objective of this study was to evaluate the roles of geo-physical, vegetation, and disturbance covariates on seasonal resource selection patterns of red pandas in a human-dominated landscape. Given their low ecological plasticity, and seasonal variation in movement ( Yonzon 1989 ; Reid et al 1991 ; Zhang et al 2009 ; Bista et al 2021b ) and space use patterns ( Yonzon 1989 ; Reid et al 1991 ; Bista et al 2022a ), we hypothesized a different degree of response to geo-physical, vegetation, and disturbance variables across seasons. We predicted that vegetation-related variables would be more important determinants of habitat utilization than geo-physical variables (such as elevation, aspect, slope, topographic position index [TPI], solar radiation, and water).…”
mentioning
confidence: 99%
“…This supports the suggestion that mine sites contain fewer resources or are riskier than favoured rocky habitat, where energy expenditure was lower—probably due to more resting or foraging behaviours there. Other small mammals show similar negative behavioural responses to anthropogenic habitats, by increasing speed [ 174 ] or tortuous movements [ 9 ]. Lower resources in mining habitats may force quolls to either traverse these areas quickly or use more energy to find food and shelter, increasing their overall food requirements [ 175 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, we found that the males occupied a relatively smaller range during the mating season. Nevertheless, the movement rate of males was high in that season, which reflects their increased effort to find mating partners and deter competing males (Bista et al 2021b). Patrolling a large home range inflates the energetic cost of movement (Jetz et al 2004, Tucker et al 2014, and animals may be reluctant to increase the range size if the cost of expanding the home range is not compensated by energy gains (McLoughlin & Ferguson 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Red pandas travelled long distances during the mating season, which indicates that they spend more time on the ground than in any other seasons (Bista et al 2021b). As predation risk is relatively high on the ground, they may have selected the low lunar photoperiod, as the predation risk during darker nights is lower (Pratas-Santiago et al 2017).…”
Section: Discussionmentioning
confidence: 99%